Peran Nelson Mandela dalam Gerakan Anti-Apartheid di Afrika Selatan 1994-1999 - Pradipta, Christian Aditya (Global and Policy Journal of International Relations, 2014)
ABSTRACTNelson Mandela is one of actor in South Africa who fought for anti-apartheid politic. He did with many ways to reach the goals. Being the member and leader of ANC is the one of his struggling. Because of his struggling against Apartheid government, he had been imprisoned. In 1990, he was out and becoming The First President through democratic ellection in 1994. When he was a President, he played the roles throgh his policies to agains apartheid politic in South African. The one of them is The Reconstruction And Development Programme (RDP). RDP is targeted to increase the citizen‟s welfare as well as economic growth. Nelson Mandela‟s anti-apartheid movement is then analyzed by using Marxism perspectives and Servant Leadership theory to see the RDP‟s effectiveness to create citizen‟s welfare.Keywords : Nelson Mandela, South Africa, RDP, apartheid.DOI:https://doi.org/10.33005/jgp.v2i01.1984